SWITCH: A tax-benefit model for Ireland linked to survey and register data - Claire Keane; Karina Doorley; Theano Kakoulidou; Seamus O'Malley (The Economic and Social Research Institute (ESRI), 2022)
We document the development and operation of the SWITCH model, Ireland's taxbenefit microsimulation model. Using the EUROMOD platform and process of creating an input model, we discuss adjustments to the underlying data, such as reweighting and uprating, aiming at improving representativeness in terms of the income tax base and beneficiaries of social welfare schemes. The validation of the model with respect to a range of external sources as well as the capabilities of the model in terms of results produced is also described.
Keywords: C81; H23; H24; I32; I38; 330; tax benefit models; income tax; databases; policy analysis